1989
DOI: 10.1039/f19898502991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxidation–reduction treatments of Pt/Al2O3 on catalytic activity and selectivity for hexane reforming

Abstract: Consecutive oxidation-reduction cycles involving successive oxidation treatments of 0.3 % Pt/AI,O, at various temperatures, each followed by a reduction treatment in hydrogen to produce active catalyst, lead to changes in catalytic activity for the reactions of n-hexane with hydrogen. Decreased activity is paralleled by changes in selectivity brought about by the increased tendency of large platinum particles towards coking. Changes in selectivity are not observed where an increase in activity occurs. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
2
4
1
Order By: Relevance
“…The results of the study with CCl4 reinforced the previously reported view 163,164,166 that the creation of oxychloroplatinum or chloroplatinum species was the important step in the redispersion process. Two sintered Pt/Al2O3 catalysts (0.6 and 1 wt.% Pt) underwent successful Pt re-dispersion at 500 °C in an oxychlorination treatment with 2% O2 in a HCl/H2O/N2 feed (H2O to HCl molar ratio of 56) for up to 8 h. 167 The treated samples were analysed using TPR, hydrogen chemisorption, In another study of a Pt/Al2O3 catalyst (which was also prechlorided with HCl during impregnation) which used HCl in the oxychlorination treatment, the effect of oxygen partial pressure (from 0 to 100%) and HCl concentration (from 0.0005 to 0.003 atm) on re-dispersion were assessed.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…The results of the study with CCl4 reinforced the previously reported view 163,164,166 that the creation of oxychloroplatinum or chloroplatinum species was the important step in the redispersion process. Two sintered Pt/Al2O3 catalysts (0.6 and 1 wt.% Pt) underwent successful Pt re-dispersion at 500 °C in an oxychlorination treatment with 2% O2 in a HCl/H2O/N2 feed (H2O to HCl molar ratio of 56) for up to 8 h. 167 The treated samples were analysed using TPR, hydrogen chemisorption, In another study of a Pt/Al2O3 catalyst (which was also prechlorided with HCl during impregnation) which used HCl in the oxychlorination treatment, the effect of oxygen partial pressure (from 0 to 100%) and HCl concentration (from 0.0005 to 0.003 atm) on re-dispersion were assessed.…”
supporting
confidence: 78%
“…161 The presence of this complex was also confirmed with UV-Vis in the re-dispersed catalysts prior to sintering. 162 The Pt redispersion process on pre chlorided Pt/Al2O3 catalysts has also been investigated in IR studies 163,164 as well as XRD and TEM. 84 It was noted that Pt re-dispersion was accompanied by an increase in Pt oxidation state; the oxidation of crystalline Pt and Pt re-dispersion were found to be conjoined processes.…”
Section: Platinummentioning
confidence: 99%
“…Note that under the reaction conditions employed, no cyclised or dehydrocyclised products were detected. This contrast with the behavior of Pt-based catalysts under equivalent conditions (Anderson et al 1989). With n-octane and n-nonane, the selectivity to hydrocracking products reached 100% at all the temperatures.…”
Section: N-alkane Hydroconversioncontrasting
confidence: 61%
“…Consecutive oxidation-reduction cycles involving successive oxidation treatments of 0.3%Pt/Al 2 O 3 c a t a l y s t w e r e m a d e a t v a r i o u s temperatures, each followed by a reduction treatment in H 2 to produce an active catalyst, lead to changes in catalytic activity for the reactions of n-hexane with H 2 . Decreased activity is paralleled by changes in selectivity brought about by the increased tendency of large Pt particles towards coking [Anderson,et al,1989]. Results show that the reforming reactions of n-hexane can be used to gain information about the state of metal particles following sintering/redispersion of Pt on alumina.…”
Section: Effect Of Sintering Over the Catalytic Activitymentioning
confidence: 83%